Evaluating the Effectiveness of Entrepreneurship Training Courses in a Developing Country - Hosseinzadeh, Majid; Razavi, Seyyed Mostafa; Hosseinzadeh, Davood (Journal of Entrepreneurship, Business and Economics; Vol 2 No 1 (2014), 2014)
Purpose- Today, entrepreneurship has become a necessity for economic development in different countries. Therefore, entrepreneurship training could be a solution in order to reach this goal. But it should be considered that for being more successful, these courses should be effective and efficient. Design/methodology/approach- In this study, a survey is conducted to evaluate the effectiveness of these courses between 265 trained individuals between in a two years period. Random sampling is done and then 113 individuals were selected to conduct the survey. Cronbach's alpha was calculated (0.967) and some hypotheses were tested. Findings- Results reveal that output effectiveness was significant, and the courses were considered to be at an acceptable level. But there were some limitations as follows: (i) lack of access to a large number of trainers, which might affect the generalization level of the findings; and (ii) finding appro-priate measures to test the mentioned hypotheses. Research Implications- The findings of this research might be used by policy makers, trainers and even tutors in the field of entrepreneurship. Originality/value- The research is among the first studies in the area of evaluating entrepreneurship training courses conducted in Iran. Research Paper Reference to this paper should be made as follows: Hosseinzadeh, M., Razavi, S. M., Hosseinzadeh, D. (2014). “Evaluating the Effectiveness of Entrepreneurship Training Courses in a Developing Country”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 1, pp. 63–73.